Water for life and food: Synergies between SDGs 2 and 6 and human rights - Mehta, Lyla; Ringler, Claudia; Varghese, Shiney (Bristol University Press, 2023)
This chapter focuses on the multiple facets and meanings of water and how it is a contested resource. It also explores linkages between SDG 6 (Clean water and sanitation) and SDG 2 (Zero hunger). Water is essential for all life and integral to the functioning of food systems; similarly, changes in our food systems are essential to achieve SDG 6. And improvements in both are needed to reduce inequities in resources and achievements. As an example, land, food and water rights often go hand in hand, and are marked by gender, caste, racial and other exclusions. The chapter highlights how accessing water for food security can be challenging for smallholders and for vulnerable and marginalized women and men, and how water allocation systems, privatization and reform processes can affect local people’s rights to water, land and food. It argues for the need to improve policy coherence across water, land and food, and concludes by making a case for strengthening the relationship between the human right to water and food, especially for marginalized women and men.